Revisitando a fenomenologia da religião: a busca pela superação da influência kantiana e as contribuições para novas perspectivas ontológicas e epistemológicas na ciência da religião - Murat, Vinícius Said (2024)
This research seeks to reflect on the possible contributions phenomenology of religion might offer to the establishment of new perspectives in the ontological and epistemological studies of Science of Religion. By exploring the centrality of the problem of defining a set object and method for the foundation of Science of Religion as an academic field, this work sought to demonstrate how the way of thinking about these two factors as separate and independent topics might imply a strong neo-Kantian influence and lead to problems that are difficult to solve. Seeking to establish a new horizon for thinking about the foundation of the Science of Religion in a non-Kantian way, we propose reflecting on both problems in their constitutive unity, i.e., that every method presupposes a defined object, and that this assumption works on itself as the basis for scientific reflection. In other words, the foundation of Science of Religion must begin with ontological reflection and, from that, derive its epistemological framework